HUBUNGAN POLA ASUH ORANG TUA DI SAAT PANDEMI COVID-19 TERHADAP KEMANDIRIAN ANAK KELOMPOK USIA 5-6 TAHUN DI KOTA TANGERANG - Dina Agustina; Ida Faridah; Lastri Mei Winarni; Warni, Warni (Nusantara Hasana Journal, 2022)
Covid-19 requires parents to learn from home nurturing independence in their children through parenting. During this pandemic, parents play a major role in encouraging children's growth and development, which implies that most children's activities are carried out at home with their parents. A significant impact can be felt by children if the family instills the nature of independence which is shown from the habits of the parents. In Indonesia, parents who do not succeed in raising their children have a proportion of cases of parental stimulation in terms of social skills and independence of preschool age children of 58.09%. In 2010, the profile of children's growth and development health problems showed 54.03% of the 3,634,505 children had good socialization and independence skills, still below the 90% target based on the Indonesian Ministry of Health. This study aims to determine the relationship between parenting patterns during the covid-19 pandemic on the independence of children aged 5-6 years in Tangerang City. This research is quantitative by using correlational analytic technique with cross sectional. The data collection instrument used a questionnaire. The population in this study was 100 people and the number of samples taken was 80 people. The location of the study was carried out in RA. Pelangi Nusantara and RA. Baiturrahman, research time from February-August. From the results of the univariate analysis, the most parenting patterns were democratic parenting as many as 69 people (86.3%), and the most independent category was the independent category as many as 70 people (87.5%). The results of the bivariate analysis with the Chi-Square obtained pvalue 0.001 <0.05 and an OR value of 11.158, meaning that respondents with democratic parenting have 11 times more chance of being independent than those with authoritarian and permissive parenting and the Pearson correlation value of 0.663 is said to be correlated or strongly related. . then Ha is accepted and Ho is rejected. It is expected that health services, especially community nursing, provide health education about good parenting for children so that they are able to form children's independence through habits or parenting patterns applied by parents.